Plasma TMAO Concentrations and Gut Microbiota Composition in Subjects with and Without Metabolic Syndrome: Results from Pilot Study - Mohammed E. Hefni; Cornelia M. Witthöft; Patrik Hellström; Ingegerd Johansson; Anders Esberg (Metabolites)
Background/Objectives: Trimethylamine N-oxide (TMAO) is a gut microbiota-dependent metabolite considered as a risk metabolite for various non-communicable diseases. This study aims to identify differences in the gut microbiota composition and concentrations of TMAO and related metabolites in subjects with and without metabolic syndrome (MetS). Methods: Plasma samples were collected following an overnight fast on two occasions from subjects with (n = 12) and without (n = 21) MetS. Feces samples were collected on the day before the first blood sampling. The gut microbiota was profiled using 16S rRNA full-gene amplification sequencing. TMAO and related methylamines were quantified using UPLC-MSMS. The fasted plasma glucose, plasma lipid profile, and HbA1c were determined, and blood pressure, circumference, height, and weight were measured. Results: A divergent gut microbiota composition was observed in feces samples from both groups. In contrast to subjects without MetS, subjects with MetS had a reduced microbial diversity, with lower Blautia glucerasea and higher Ruminococcus torques—a pattern associated with (increased) inflammation. Trimethylamine (TMA)-producing bacteria were low in abundance across both groups. While plasma TMAO and related methylamines displayed no significant differences between both groups, L-carnitine was elevated (p = 0.0191) in subjects with MetS. A strong positive correlation was detected between TMAO and TMA (r = 0.439, p = 0.003), with a tendency to correlate with carnitine (r = 0.212, p = 0.087). Conclusions: Subjects with MetS were characterized by gut microbiota favoring inflammation-associated species but not TMA producers. This suggests that TMAO may not play a role in MetS subjects without overt comorbidities, e.g., CVD or T2D. The influence of the gut microbiota on early MetS is likely mediated through inflammatory mechanisms driven by specific bacterial shifts rather than TMAO production.